REFLEKSI KEPEMIMPINAN UMAR BIN ABDUL AZIZ DALAM MENSEJAHTERAKAN RAKYAT MELALUI PERANTARA ZAKAT - Muhamad Irhamdi; Dimas Ramadhani Adi Yusuf; Nyi Ayu Siti Aisyah (Mudabbir: Jurnal Manajemen Dakwah, 2020)
Zakah is one of the five pillars of Islam. It is a form of obligatory charity that has the potential to ease the suffering of millions. Zakah is the practice where every Muslim gives 2.5 percent of their earnings if it has reaches haul, which is one Hijriah year (the completion period for a zakah asset). The most well-known zakah around people is called zakah al-fitr, a type of zakah that is only issued in the holy month of Ramadhan. During this time, people are just assuming that zakah is one of the obligations that need to be fulfilled. In fact, if examined more deeply, then there will be lots of benefits that can be obtained from doing the charity. One of the famous khilafah leaders that can show his success in carrying out the zakah during his era of leadership is Umar bin Abdul Aziz ra. Through zakah, he was able to proper all the lives of his people. He was also able to change the status of Muslims in his era from mustahik (those who deserve to get zakah) into muzakki (those who can pay for zakah). Indonesia, as one of the largest Muslim countries in the world, should look back at the history of how people before them succeeded in doing zakah. What's more, Indonesia itself has established the Agency or Institution of zakah that should have been able to provide some results. It is expected that with the establishment of these agency, then the economy in Indonesia can be increased, though only slightly. It has never been easy. But at least, they have tried their best. Mutual trust between the community and the officials had long been eroded. The government and those religious leaders should be able to restore mutual trust between them and also with the community. Because success cannot be achieved by just only one person, but there must be others that can support them.